2013
DOI: 10.1186/1475-2859-12-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction without methanol: novel regulated promoters enable high-level expression in Pichia pastoris

Abstract: BackgroundInducible high-level expression is favoured for recombinant protein production in Pichia pastoris. Therefore, novel regulated promoters are desired, ideally repressing heterologous gene expression during initial growth and enabling it in the production phase. In a typical large scale fed-batch culture repression is desired during the batch phase where cells grow on a surplus of e.g. glycerol, while heterologous gene expression should be active in the feed phase under carbon (e.g. glucose) limitation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
113
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 26 publications
0
113
0
1
Order By: Relevance
“…Both systems have their drawbacks, particularly methanol as a substrate and P GAP as a non-inducible promoter (Kovar et al 2010; Mellitzer et al 2014). Systems are sought in which production can be regulated without using methanol induction (Hartner et al 2008; Prielhofer et al 2013; Stadlmayr et al 2010; Vogl and Glieder 2013; Vogl et al 2016). Such carbon source-dependent promoters are either synthetic variants of the natural P AOX1 promoter, generated by selected (short) sequence deletions/insertions (Hartner et al 2008), or newly identified natural carbon source-regulated promoters (Prielhofer et al 2013; Stadlmayr et al 2010; Vogl et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both systems have their drawbacks, particularly methanol as a substrate and P GAP as a non-inducible promoter (Kovar et al 2010; Mellitzer et al 2014). Systems are sought in which production can be regulated without using methanol induction (Hartner et al 2008; Prielhofer et al 2013; Stadlmayr et al 2010; Vogl and Glieder 2013; Vogl et al 2016). Such carbon source-dependent promoters are either synthetic variants of the natural P AOX1 promoter, generated by selected (short) sequence deletions/insertions (Hartner et al 2008), or newly identified natural carbon source-regulated promoters (Prielhofer et al 2013; Stadlmayr et al 2010; Vogl et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Systems are sought in which production can be regulated without using methanol induction (Hartner et al 2008; Prielhofer et al 2013; Stadlmayr et al 2010; Vogl and Glieder 2013; Vogl et al 2016). Such carbon source-dependent promoters are either synthetic variants of the natural P AOX1 promoter, generated by selected (short) sequence deletions/insertions (Hartner et al 2008), or newly identified natural carbon source-regulated promoters (Prielhofer et al 2013; Stadlmayr et al 2010; Vogl et al 2016). For example, recombinant protein production can be repressed during batch phase with excess glycerol, and recombinant gene expression can be initiated during substrate-limited fedbatch cultivation with glucose (Prielhofer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, they are still commonly referred to as P. pastoris . In recent years, the genetic toolbox for P. pastoris has been markedly expanded with several newly discovered native promoters, synthetic promoters and other regulatory elements891011. The construction of optimized strains and vectors enabled new applications, e.g.…”
mentioning
confidence: 99%
“…A novel regulated promoter has recently been identified from a high-affinity glucose transporter gene (GTH1) which is repressed by glycerol. 9 Since P GTH1 is responsive to carbon source depletion it should represent an attractive and cheap alternative to other regulated systems that rely on the addition of an external source of the inducing agent. Recently, 2 inducible promoters from the K. phaffii rhamnose utilization pathway were proposed for the production of food-grade and therapeutically important recombinant proteins.…”
Section: Inducible and Constitutive Promotersmentioning
confidence: 99%
“…18 Promoter libraries have already been constructed using not only random mutagenesis methods but also with specific synthetic core promoter sequences derived from wild-type promoter alignments. 9,19 The P GAP sequence has also been manipulated through error-prone PCR for the construction of a GAP-promoter library with strengths varying from »0,6% to 19,6-fold of that of the wild-type P GAP . 20 …”
Section: 17mentioning
confidence: 99%